Eduwisata: Promosi Wisata Berbasis Edukasi untuk Meningkatkan Daya Tarik Wisata Taman Anyar di Desa Wisata Penarungan - Ni Nyoman Arini; Nanda, I Putu Jaya; Saputra, I Kadek Saputra; Rijastawa, I Kadek Heri; Adnyana, I Nyoman Putra; Ardita , I Putu Mega (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
The development of community-based tourism villages has the potential to improve local economic welfare, and preserve culture, and the environment. Taman Anyar as one of the attractions of educational tourism in Penarungan Tourism Village, faces obstacles in utilizing digital media as a promotional medium for educational tourism. Currently, managers only use Instagram and Facebook as promotional media, with the majority of the content disseminated in the form of photos and video recordings that have not gone through the editing process. Based on the results of interviews with the manager of Taman Anyar, the Real Work Lecture team of Triatma Mulya University identified the need to strengthen digital-based promotion to strengthen the attraction of educational tourism in Taman Anyar. This activity aims to strengthen the attraction of educational tourism and tourists' interest in local tourism potential through the presentation of informative content and the use of digital media. In addition, this activity also aims to provide insight for local communities in managing and developing sustainable educational tourism. The methods used in this activity are observation, interviews, and documentation. The results of this activity show that with the seminars and trainings, managers and local communities increasingly understand the importance of digital promotional content in attracting tourists and sustainable management of educational tourism. In addition, assistance in creating promotional video content and booklets uploaded to digital platforms, such as YouTube and Instagram, introduces Taman Anyar to a wider audience. With this activity, it is hoped that Taman Anyar can be better known by domestic and foreign tourists, increase tourist visits, and have a positive impact on the local economy and the preservation of Balinese culture.